2003
DOI: 10.1140/epja/i2002-10079-7
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the η production in proton-proton collisions with the COSY time-of-flight spectrometer

Abstract: The reaction pp → ppη was measured at excess energies of 15 and 41 MeV at an external target of the Jülich Cooler Synchrotron COSY with the Time of Flight Spectrometer. About 25000 events were measured for the excess energy of 15 MeV and about 8000 for 41 MeV. Both protons of the process ppη were detected with an acceptance of nearly 100 % and the η was reconstructed by the missing mass technique. For both excess energies the angular distributions are found to be nearly isotropic. In the invariant mass *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…The near-threshold η meson production in nucleonnucleon collisions has been investigated extensively in the CELSIUS, COSY and SATURNE facilities. The results determined by different experiments for the total (Bergdolt et al, 1993;Calen et al, 1996;Chiavassa et al, 1994;Hibou et al, 1998;Moskal et al, , 2010Smyrski et al, 2000) and differential (Abdel-Bary et al, 2003;Moskal et al, , 2010Petren et al, 2010) crosssections for the pp → ppη and for the quasi-free pn → pnη reactions (Calen et al, 1996(Calen et al, , 1998Moskal et al, 2009) are consistent within the estimated uncertainties. In the different experiments η mesons could be produced up to excess energy E of 92 MeV at CELSIUS, 502 MeV at COSY and 593 MeV at SATURNE.…”
Section: η-And η -Nucleon Interactionssupporting
confidence: 69%
See 1 more Smart Citation
“…The near-threshold η meson production in nucleonnucleon collisions has been investigated extensively in the CELSIUS, COSY and SATURNE facilities. The results determined by different experiments for the total (Bergdolt et al, 1993;Calen et al, 1996;Chiavassa et al, 1994;Hibou et al, 1998;Moskal et al, , 2010Smyrski et al, 2000) and differential (Abdel-Bary et al, 2003;Moskal et al, , 2010Petren et al, 2010) crosssections for the pp → ppη and for the quasi-free pn → pnη reactions (Calen et al, 1996(Calen et al, , 1998Moskal et al, 2009) are consistent within the estimated uncertainties. In the different experiments η mesons could be produced up to excess energy E of 92 MeV at CELSIUS, 502 MeV at COSY and 593 MeV at SATURNE.…”
Section: η-And η -Nucleon Interactionssupporting
confidence: 69%
“…The pole parameter µ fitted from experiment is ≈ 0.75 MeV for the η (Wilkin, 2016). Measurements of the differential cross-sections for η production at E = 15.5 MeV and at E = 41 MeV (Abdel-Bary et al, 2003) are consistent with isotropic η production within the statistical errors, though at 41 MeV the accuracy of the data do not exclude a few per cent contribution from higher partial waves. For η production, the differential cross sections measured at SATURNE (Balestra et al, 2000) at E = 143.8 MeV and at COSY (Khoukaz et al, 2004) at E = 46.6 MeV are consistent with pure Ss-wave production with ≈ 10% level higher partial wave contributions possible within the experimental uncertainties.…”
Section: η-And η -Nucleon Interactionsmentioning
confidence: 80%
“…where C 1 and C 2 are treated as free parameters. For Q ¼ 15 MeV, the angular distribution of the cross section (dσ=dΩ η ) is assumed to be constant as determined by the COSY-11 [16] and COSY-TOF [15] At Q ¼ 15 MeV, we find no evidence for partial waves beyond s-wave production. At Q ¼ 72 MeV, we find evidence for significant contributions of higher partial waves.…”
mentioning
confidence: 84%
“…Previous studies by the CELSIUS [10][11][12][13], COSY [14][15][16][17][18], and SATURNE [19][20][21] experiments of the total and differential cross sections for η meson production in pp and pn collisions revealed that the η meson is predominantly produced via the excitation of one of the nucleons to the S 11 current via exchange of virtual mesons with the subsequent decay into the proton-η pair. This conclusion was obtained from the observation of a large η production cross section relative to the η 0 meson production and the isotropic angular distribution of the η mesons in the center-of-mass (c.m.)…”
mentioning
confidence: 99%
“…In the latter reaction, there has been observed a significant enhancement of the cross section for larger pp invariant-mass values compared to that given by the phase-space plus the pp final-state interaction (FSI) [23,27]. One of the possible explanations for this enhancement is the 054004-11 relatively strong Nη FSI.…”
Section: N N → N Nηmentioning
confidence: 99%